Estimating the Prevalence and Risk Factors of Obstetric Fistula in Ethiopia: Results from Demographic and Health Survey - Gedefaw G; Wondmieneh A; Getie A; Bimerew M; Demis A (Dove Medical Press, 2021)
Getnet Gedefaw,1 Adam Wondmieneh,2 Addisu Getie,2 Melaku Bimerew,2 Asmamaw Demis2 1School of Midwifery, College of Health Sciences, Woldia University, Woldia, Ethiopia; 2School of Nursing, College of Health Sciences, Woldia University, Woldia, EthiopiaCorrespondence: Getnet Gedefaw Email gedefawget@gmail.comIntroduction: Obstetric fistula is the most common obstetric problem in low- and middle-income countries where maternal care is inaccessible. Obstetric fistula has serious social and economic consequences resulting in devastating health problems for women. There is a lack of national studies that show the burden of obstetric fistula and risk factors; as a result, this study aimed to estimate the prevalence of obstetric fistula, its symptoms, and risk factors in Ethiopia.Methods: A population-level cross-sectional study was conducted with a total of 7590 women who gave birth in the last 5 years, using data from the 2016 Ethiopian Demographic and Health Survey. Complex sample analysis and normalized weighting were used to compensate for the disproportionate sampling in the survey. A multivariable logistic regression model was fitted to find a significant association between obstetric fistula and covariates. Both odds ratios (crude and adjusted) with their corresponding 95% confidence intervals (CI) were reported.Results: Among the 7590 women having given birth in the last 5 years, 32 (0.42%) women with obstetric fistula were identified. Of these, 64% developed obstetric fistula after live birth and 23.1% developed obstetric fistula after stillbirth. More than 72.8% were associated with prolonged and very difficult labor. No history of contraceptive use (AOR = 3.43; 95% CI: 1.05- 11.21), having a big problem of distance from the health facility (AOR = 3.7; 95% CI: 1.05- 11.21), early marriage (AOR = 1.52; 95% CI: 1.12- 3.5), and being a rural resident (AOR = 1.5; 95% CI:1.2- 5.05) were risk factors associated with obstetric fistula.Conclusion: This study finding revealed that obstetric fistula is the most common devastating obstetric problem in Ethiopia. Early marriage, early initiation of sexual intercourse, distance from the health facility, no history of contraceptive use, and rural residence were the predisposing factors to develop an obstetric fistula. Thus, interventions should focus on creating community awareness regarding early marriage and its consequences, early seeking of health facility visiting, and avoiding unintended pregnancy to minimize the subsequent complications.Keywords: obstetric fistula, vaginal fistula, risk factors, Ethiopia